Analisis Ruang Terbuka Hijau (RTH) Taman Kota Nyahu Papan Taliwu Kota Palangka Raya serta Optimalisasi Fungsinya bagi Keluarga - Fahrul Fahlevi; Aprianur Aprianur; Aufa Ahmad; Markcelino Markcelino; Arjunna Arjunna; Febriaman Zalukhu; Sri Mujiarti Ulfah; Suprayitno Suprayitno (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the existing condition of Nyahu Papan Taliwu City Park in Palangka Raya and to formulate strategies for optimizing its function as a family-friendly public space. The research employed a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and documentation. Data collection was conducted on May 11, 2026, through one comprehensive field observation and three interview sessions. Three informants participated: two local community members who regularly use the park and one security officer. Data validation was performed using source triangulation and method triangulation. The findings indicate that Nyahu Papan Taliwu City Park generally fulfills its role as a family-friendly public green open space, supported by facilities such as children's playgrounds, jogging tracks, exercise equipment, gazebos, flower gardens, CCTV, and security officers. Public perception of the park is highly positive, with most respondents considering the park adequate and comfortable. The study reveals that park optimization does not require the addition of numerous new facilities, but should instead prioritize routine maintenance and the revitalization of existing infrastructure. A significant issue identified is that some visitors continue to smoke in the children's play area, posing health risks to children and reducing the park's effectiveness as a child-friendly environment. The study concludes that the government should focus on three main aspects: periodic maintenance and revitalization of facilities, stricter enforcement of no-smoking regulations, and improved supervision and public awareness among visitors.